2021
DOI: 10.21837/pm.v19i16.953
|View full text |Cite
|
Sign up to set email alerts
|

Application of Machine Learning in Analysing Historical and Non-Historical Characteristics of Heritage Pre-War Shophouses

Abstract: Real estate is complex and its value is influenced by many characteristics. However, the current practice in Malaysia shows that historical characteristics have not been given primary consideration in determining the value of heritage properties. Thus, the accuracy of the values produced is questionable. This paper aims to determine whether the historical characteristics of the pre-war shophouses at North-East Penang Island, Malaysia contribute any significance to their value. Several Machine Learning algorith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In another work, the property prices in China is modelled using linear regression, SVM regression, neural network regression and the k-nearest neighbour approach and it is shown that the SVM regression has the best performance indicators [18]. Similarly, the housing prices in Malaysia is modelled using random forest, decision tree, lasso regression, ridge regression and linear regression and it is concluded that the random forest approach has the best accuracy [19]. Similarly, the property values in Kota Bharu, Malaysia are modelled using various regression models where it is demonstrated that the rank transformation regression model has better performance compared to the ordinary least squares model [20].…”
Section: Literature Surveymentioning
confidence: 99%
“…In another work, the property prices in China is modelled using linear regression, SVM regression, neural network regression and the k-nearest neighbour approach and it is shown that the SVM regression has the best performance indicators [18]. Similarly, the housing prices in Malaysia is modelled using random forest, decision tree, lasso regression, ridge regression and linear regression and it is concluded that the random forest approach has the best accuracy [19]. Similarly, the property values in Kota Bharu, Malaysia are modelled using various regression models where it is demonstrated that the rank transformation regression model has better performance compared to the ordinary least squares model [20].…”
Section: Literature Surveymentioning
confidence: 99%